Development Of A Scientific-Based Special Relativity E-Module To Improve Critical Thinking Ability Physics Education Students - Amin, Ahmad; Badeni, Badeni; Koto, Irwan (LPPM Universitas PGRI Sumatera Barat, 2025)
This research aims to develop a scientifically based physics e-module to improve students' critical thinking skills, which are valid, practical and effective. This type of research is (R & D) with a 4D development model (define, design, develop and disseminate). The research sample was physics education students in the sixth semester of PGRI Silampari University. Data collection techniques use questionnaires and tests, research instruments in the form of questionnaires and test questions. The validation results from language experts averaged 0.83 in the very valid category, with inter-rater reliability of 42%, a moderate level of agreement. The validation results from media experts averaged 0.88 in the very valid category, with inter-rater reliability of 57%, a moderate level of agreement. The validation results from material experts averaged 0.86 in the very valid category, with inter-rater reliability of 63%, a strong level of agreement. The lecturers' practical response to the scientific-based physics e-module obtained a practicality percentage of 82.5% in the very practical category. The practical response of the limited group of students (6 students) to the scientific-based physics e-module obtained an average percentage of practicality of 88.3% in the very practical category. Based on calculations from the critical thinking questionnaire, the critical thinking percentage was 80% in the high category. Apart from that, from the test results that used questions with critical thinking indicators, an average pre-test score was 35,67 and an average post-test score was 78,85 with an average Gain test score of 0.67 in the medium category. So it can be concluded that the scientific-based e-module developed has been declared valid, practical and effective, for improving students' critical thinking abilities